Infrared thermal modulation endoscopy for label-free tumor detection - Suhyeon Kim; Gyungseok Oh; Young Ro Kim; Euiheon Chung; Hyuk-Sang Kwon (Scientific Reports)
Abstract In optical imaging of solid tumors, signal contrasts derived from inherent tissue temperature differences have been employed to distinguish tumor masses from surrounding tissue. Moreover, with the advancement of active infrared imaging, dynamic thermal characteristics in response to exogenous thermal modulation (heating and cooling) have been proposed as novel measures of tumor assessment. Contrast factors such as the average rate of temperature changes and thermal recovery time constants have been investigated through an active thermal modulation imaging approach, yielding promising tumor characterization results in a xenograft mouse model. Here, to assess its clinical potential, we developed and deployed an endoscopic infrared thermal modulation imaging system, incorporating anti-reflection germanium lenses. Employing tissue cooling, we evaluated the feasibility of detecting in situ tumors in a syngeneic rectal tumor mouse model. Consequently, early-stage tumors were successfully localized and evaluated based on their heat signatures. Notably, tumors exhibited a higher rate of temperature change induced by thermal modulation compared to adjacent tissues. Through the introduction of this label-free technology, Infrared Thermal Modulation Endoscopy (ITME), our study showcased an effective method for optically delineating and assessing solid tumors. This innovative diagnostic technology holds significant promise for enhancing our ability to detect, classify, and characterize abnormal tissues.